Analysis of foundation system partially on shafts and partially on mat foundation and its influence on adjacent existing drilled shafts. Issue 4 (7th August 2016) - Jha, Pravin; Kumar, Sanjeev; Kolay, Prabir
Abstract : Construction of large structures close to each other is a common practice as long as interaction between the foundations of these structures is appropriately considered. A very limited amount of literature is available to analyze and design deep and shallow foundations when they are constructed adjacent to each other. The authors have recently been involved in a project where a large structure was supposed to be constructed on drilled shafts adjacent to another existing large structure founded on drilled shafts socketed into the bedrock. Several of the shafts for the proposed structure were already in place. However, due to a change in the project requirements, the owner wanted to know if it is possible to eliminate the remainder of the shafts and change the foundation type from drilled shafts to mat foundation resting on a layer of compacted crushed stone. This change would cause a part of the proposed structure to rest on subsurface having very high stiffness compared to the other part. In addition, the change would cause different interaction with the foundation of the adjacent structure. This paper presents more detailed information about the project, analysis procedure used, results, and conclusions developed which are useful for practicing engineers to make informed decisions when different types of foundations are constructed close to each other.